Operational management analysis regarding optimization of making liquid smoke with cyclone distillation technology - Haryadi, Dudi; Fathussalam, Muhammad; Giffari, Fahri Rijal; Ainun, Khairunissa; Yuwono, Indra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study focuses on evaluating the yield and characteristics of liquid smoke obtained from palm kernel shell, mesocarp fiber, and oil palm frond biomass. The objective of the research is to determine both the percentage yield of liquid smoke produced per gram of palm oil solid waste and characterize the compounds present in the liquid smoke. Solid samples of palm oil waste components (shells, fibers, and fronds) were prepared and subjected to pyrolysis using Distillation Cyclone technology. Liquid smoke produced was then analyzed to determine the concentration of phenolic compounds. The study found that the yield of liquid smoke varied among different palm oil solid waste components, with a higher yield observed from oil palm shell biomass compared to others. Furthermore, the liquid smoke from all three biomass sources exhibited significant concentrations of phenolic compounds, indicating its potential as a natural pesticide ingredient. This research highlights the potential of utilizing palm oil solid waste for value-added products such as liquid smoke, contributing to waste management and sustainable agricultural practices. The findings provide insights for further research and development of eco-friendly pest control solutions utilizing liquid smoke-derived compounds.